EFEKTIVITAS DOSIS REFISOL TERHADAP PURUNAN ANGKA KUMAN PADA LANTAI BANGSAL PERAWATAN PENYAKIT DALAM RUMAH SAKIT UMUM DAERAH KABUPATEN KARANGANYAR 2003 - Ninuk . Krisetyowati; Margo . Utomo (Jurnal Kesehatan Masyarakat Indonesia, 2004)
ABSTRACT Background: Hospital sanitary especially the sterilisation and disinfectant activities has a function to control the existence of germs to prevent nosocomial infection. This is considered important because the number of germs at the General Hospital Karanganyar is more than l0 germs/cmz . Disinfecting activity is usually done by mopping .the floor using Refisol clisinfectant. However, nobody knows how much dose is needed to effectively reduce the number of germs on the floor. Objective: to find out the effective dose of the Refisol disinfectant in reducing the rumber of germs on the floor. Method. This experimental research is applied pre-test control group design. The subject is the floor in four wards that have the same condition. The research procedure is by having a post test by wiping the floor before mopping and count the germs. Then, tredt the floor by giving some dose of Refisol desinfectant (30, 40, and 50 mL), and later, test it again by wiping the floor after mopping and count the germs, while the contol group only cleaning the floor with water. The data is analyzed by using the Paired Sample T-Test and one way Analysis of variance. Result: in the dose of 30 mL there is a reduction of germsupto 28,8%. This number increases in the dose of 40mLt o 39,81%,in the dose of 50mL to 54,17%(the highest). Test in control treatment gain t:5,458 and p:0,002, in 30 mL dose t:10,102 and p:0,012, in 40 mL t:5,384 and p:0,013 while 50 mL dose is t:5,451 and p:0,012. It means that there is a significant change in the number of germs before and after treatments. Conclusion, The dose of Refisol disidectant incluenced to number of floor germs reducing. Keywords : disinfectant dose, Refisol, the decrease of floor germs number